Penyelesaian Perselisihan Hubungan Industrial karena Pemutusan Hubungan Kerja (PHK) Dihubungkan dengan UU No.2 Tahun 2004 tentang Penyelesaian Perselisihan Hubungan Industrial - Muhammad Rasyiq Fadlan; Rini Irianti Sundary (Bandung Conference Series: Law Studies, 2022)
Abstract. Termination of Employment Relationship (Layoff) is the termination of the employment relationship due to a matter that results in the termination of the rights and obligations between the worker/laborer and the entrepreneur as regulated in Article 1 Number 25 of Law Number 13 of 2003 concerning Manpower. The problem in writing this is, how the actions of employees against companies that do lay offs are not in accordance with the period of service written in Article 156 of Law No. 13 of 2003 concerning Employment, and how is the legal protection for workers in Termination of Employment (Layoff). The results of the study indicate that disputes over termination of employment must be resolved by Bipartite, Mediation, Conciliation, and Arbitration, if it does not produce results, then the lawsuit is submitted to the Industrial Relations Court. The settlement of disputes over termination of employment at the Industrial Relations Court is carried out in accordance with the provisions of Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes. This study uses a juridical approach with research specifications using analytical descriptive, the type of data used is secondary data, with library research data collection techniques and data analysis techniques using qualitative juridical. Based on the analysis, the results of this study: (1) Knowing the settlement of industrial relations disputes and (2) Knowing what legal protections are obtained by the workers and the company based on Decision Number 113/Pdt/SUS-P.H.l/2020/PN.BDG through the Court Industrial relations. Abstrak. Pemutusan Hubungan Kerja (PHK) adalah pengakhiran hubungan kerja karena suatu hal yang mengakibatkan berakhirnya hak dan kewajiban antara pekerja/buruh dan pengusaha diatur dalam Pasal 1 Angka 25 Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan. Permasalahan dalam penulisan ini adalah, bagaimana tindakan karyawan terhadap perusahaan yang melakukan PHK tidak sesuai dengan masa kerja yang tertulis di Pasal 156 Undang-undang No 13 Tahun 2003 Tentang Ketenagakerjaan, dan Bagaimana perlindungan hukum bagi pekerja dalam Pemutusan Hubungan Kerja (PHK). Hasil penelitian menunjukkan bahwa perselisihan pemutusan hubungan kerja harus di upayakan diselesaikan Bipartit, Mediasi, Konsiliasi, dan Arbitrase, apabila tidak membuahkan hasil barulah gugatan ajukan ke Pengadilan Hubungan Industrial. Penyelesaian perselisihan pemutusan kerja di Pengadilan Hubungan Industrial dilakukan sesuai dengan ketentuan dalam Undang-Undang Nomor 2 Tahun 2004 tentang Penyelesaian Perselisihan Hubungan Industrial. Penelitian ini menggunakan metode pendekatan yuridis dengan spesifikasi penelitian menggunakan deskriptif analitis, jenis data yang digunakan adalah data sekunder, dengan teknik pengambilan data studi kepustakaan dan Teknik analisis data menggunakan yuridis kualitatif. Berdasarkan analisis, hasil dari penelitian ini : (1) Mengetahui penyelesaian perselisihan hubungan industrial dan (2) Mengetahui perlindungan hukum apa yang didapatkan oleh pihak pekerja dan pihak perusahaan berdasarkan Putusan Nomor 113/Pdt/SUS-P.H.l/2020/PN.BDG melalui Pengadilan Hubungan Industrial